Pengaruh Pendekatan Konstrukivisme dengan Strategi Group Investigation terhadap Pemahaman Konsep Matematis Siswa SMP Negeri 99 Jakarta - Monika Aprilia; Tri Murdiyanto; Anny Sovia (Jurnal Riset Pendidikan Matematika Jakarta, 2023)
This study aims to investigate the effect of the constructivism approach with the group investigation strategy on students' understanding of mathematical concepts at SMP Negeri 99 Jakarta. This research method is a quasi-experimental method with a post-test only control group design. The research instrument used was an instrument to test the ability to understand mathematical concepts in the form of 5 essay questions which had been declared valid and reliable. The target population of the research were all students of SMP Negeri 99 Jakarta with class VIII students of SMP Negeri 99 Jakarta as an affordable population. The sampling technique used purposive sampling selected four classes then with cluster random sampling the research sample was obtained, namely students in class VIII-A and VIII-C of SMP Negeri 99 Jakarta. Testing the statistical hypothesis t-test with a significance level of